The Role of Dayah Education in the Implementation of Islamic Sharia in Aceh - Mubarak, Fadhil; Alfarasyi, Akram; Afifulloh, Mohammad; Rahmati, Arinal (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2023)
This study aims to find out the roles of Dayah as an Islamic educational institution in providing understanding and awareness for Acehnese regarding the implementation of Islamic law in Aceh. This study uses a qualitative research method with a multi-case study approach. The locus of research is three Islamic boarding schools (dayah) in Aceh with three different models. Data was taken from documentation and in-depth interviews with students and teachers at related institutions. The sampling technique used a combination of purposive and snowball techniques. Data collection uses in-depth interviews and documentation techniques. Data analysis uses an interactive analysis model from Miles and Huberman. Triangulation techniques are used to ensure the validity of the data. The results of this study indicate that dayah education has at least two main roles. First, the role of creating a society that can accept Islamic law properly. Second, the role of forming a government that can create Islamic Sharia regulations that follow the culture of the Acehnese. For public education, this can be channeled by transferring understanding from teungku dayah to teungku imum through the Aceh government as an intermediary. Dayah alumni can also help in terms of the role of public education with da'wah via behavior, speech, and writing. Practically, the dayah teacher plays a role in implementing Islamic law in four roles: teacher, practitioner of sharia, observer, and mentor. In conclusion, Islamic education in Aceh has two key roles: shaping society to follow Islamic law and adapting Sharia regulations to Acehnese culture. Recommendations include seeking guidance from qualified clerics, and stakeholders should prioritize their roles in achieving this. Future research on Aceh's Islamic law should consider local socio-religious and socio-cultural factors.